Activation of Surface Hydroxyl Groups by Modification of H-Terminated Si(111) Surfaces - Thissen, Peter; Peixoto, Tatiana; Longo, Roberto C.; Peng, Weina; Schmidt, Wolf Gero; Cho, Kyeongjae; Chabal, Yves J. (Journal of the American Chemical Society)

Interplay between metal-free phthalocyanine molecules and Au(110) substrates - Rauls, E.; Schmidt, Wolf Gero; Pertram, T.; Wandelt, K. (Surface Science)

Adsorption of OH and H at the LiNbO3(0001) surface - Hölscher, R.; Sanna, S.; Schmidt, Wolf Gero (physica status solidi (c))

Atomic-resolution imaging of the polar (0001¯) surface of LiNbO3in aqueous solution by frequency modulation atomic force microscopy - Rode, S.; Hölscher, R.; Sanna, S.; Klassen, S.; Kobayashi, K.; Yamada, H.; Schmidt, Wolf Gero; Kühnle, A. (Physical Review B)

Atomistic Picture of Charge Density Wave Formation at Surfaces - Wall, Simone; Krenzer, Boris; Wippermann, Stefan; Sanna, Simone; Klasing, Friedrich; Hanisch-Blicharski, Anja; Kammler, Martin; Schmidt, Wolf Gero; Horn-von Hoegen, Michael (Physical Review Letters)

Linear and nonlinear optical response of LiNbO3 calculated from first principles - Riefer, Arthur; Sanna, Simone; Gavrilenko, Alexander V.; Schmidt, Wolf Gero (IEEE Transactions on Ultrasonics, Ferroelectrics, and Frequency Control)

Fingerprints of order and disorder in the electronic and optical properties of crystalline and amorphous TiO2 - Landmann, M.; Köhler, T.; Köppen, S.; Rauls, E.; Frauenheim, T.; Schmidt, Wolf Gero (Physical Review B)

Substrate Induced Thermal Decomposition of Perfluoro-Pentacene Thin Films on the Coinage Metals - Schmidt, Christian; Breuer, Tobias; Wippermann, Stefan; Schmidt, Wolf Gero; Witte, Gregor (The Journal of Physical Chemistry C)

Ferroelectric phase transition in LiNbO3: Insights from molecular dynamics - Sanna, S.; Schmidt, Wolf Gero (IEEE Transactions on Ultrasonics, Ferroelectrics and Frequency Control)

Polarization-dependent methanol adsorption on lithium niobate Z-cut surfaces - Riefer, A.; Sanna, S.; Schmidt, Wolf Gero (Physical Review B)

Quantitative description of interactions between linear organic chromophores - Denis, Jean-Christophe; Schumacher, Stefan; Galbraith, Ian (The Journal of Chemical Physics)
To model intermolecular excitation transfer between organic chromophores in the framework of Förster theory, the interaction matrix element is needed for all relative orientations and separations of chromophores. Simulations of extended multi-chromophoric systems thus require a fast but reliable approximation scheme to calculate these dipole interactions. By means of a comparative study of the dipole approximation with quantum chemistry, we demonstrate that the usual line-dipole theory, while suitable for short molecules, breaks down for longer molecules with inter-molecular separations similar to or smaller than the length of the interacting chromophores; a limit that is typically found in conjugated polymer thin films. As a remedy, we propose an improved way of distributing the sub-dipole moments within a line which provides results in very good agreement with the quantum chemistry, and is still simple enough to be used in large scale simulations.

Spectral Signatures of Polarons in Conjugated Co-polymers - Wiebeler, Christian; Tautz, Raphael; Feldmann, Jochen; von Hauff, Elizabeth; Da Como, Enrico; Schumacher, Stefan (The Journal of Physical Chemistry B)

Characteristics of real life contexts and their influence on student interest in learning chemistry - Fechner, Sabine; van Vorst, Helena (Ebook of the ESERA 2011 conference. Science learning and citizenship (S. 135–141))

In-Si(111)(4 × 1)/(8 × 2) nanowires: Electron transport, entropy, and metal-insulator transition - Schmidt, Wolf Gero; Wippermann, S.; Sanna, S.; Babilon, M.; Vollmers, N. J.; Gerstmann, Uwe (physica status solidi (b))

Dynamics of fluorescence depolarisation in star-shaped oligofluorene-truxene molecules - Montgomery, Neil A.; Hedley, Gordon J.; Ruseckas, Arvydas; Denis, Jean-Christophe; Schumacher, Stefan; Kanibolotsky, Alexander L.; Skabara, Peter J.; Galbraith, Ian; Turnbull, Graham A.; Samuel, Ifor D. W. (Physical Chemistry Chemical Physics)

Hybrid functionals and GW approximation in the FLAPW method - Friedrich, Christoph; Betzinger, Markus; Schlipf, Martin; Blügel, Stefan; Schindlmayr, Arno (Journal of Physics: Condensed Matter)
We present recent advances in numerical implementations of hybrid functionals and the GW approximation within the full-potential linearized augmented-plane-wave (FLAPW) method. The former is an approximation for the exchange–correlation contribution to the total energy functional in density-functional theory, and the latter is an approximation for the electronic self-energy in the framework of many-body perturbation theory. All implementations employ the mixed product basis, which has evolved into a versatile basis for the products of wave functions, describing the incoming and outgoing states of an electron that is scattered by interacting with another electron. It can thus be used for representing the nonlocal potential in hybrid functionals as well as the screened interaction and related quantities in GW calculations. In particular, the six-dimensional space integrals of the Hamiltonian exchange matrix elements (and exchange self-energy) decompose into sums over vector–matrix–vector products, which can be evaluated easily. The correlation part of the GW self-energy, which contains a time or frequency dependence, is calculated on the imaginary frequency axis with a subsequent analytic continuation to the real axis or, alternatively, by a direct frequency convolution of the Green function G and the dynamically screened Coulomb interaction W along a contour integration path that avoids the poles of the Green function. Hybrid-functional and GW calculations are notoriously computationally expensive. We present a number of tricks that reduce the computational cost considerably, including the use of spatial and time-reversal symmetries, modifications of the mixed product basis with the aim to optimize it for the correlation self-energy and another modification that makes the Coulomb matrix sparse, analytic expansions of the interaction potentials around the point of divergence at k=0, and a nested density and density-matrix convergence scheme for hybrid-functional calculations. We show CPU timings for prototype semiconductors and illustrative results for GdN and ZnO.

Growth of cubic GaN on 3C–SiC/Si (001) nanostructures - Kemper, R.M.; Hiller, L.; Stauden, T.; Pezoldt, J.; Duschik, K.; Niendorf, T.; Maier, H.J.; Meertens, D.; Tillmann, K.; As, D.J.; Lindner, Jörg (Journal of Crystal Growth)
We report on the molecular beam epitaxy growth of cubic GaN on 3C–SiC (001) nanostructures. Transmission electron microscopy (TEM) studies show phase-pure cubic GaN crystals with a low defect density on top of the post shaped 3C–SiC nanostructures and GaN grown on their sidewalls, which is dominated by {111} planar defects. The nanostructures, aligned parallel and perpendicular to the [110] directions of the substrate, are located in anti-phase domains of the 3C–SiC/Si (001) substrate. These anti-phase domains strongly influence the optimum growth of GaN layers in these regions. TEM measurements demonstrate a different stacking fault density in the cubic GaN epilayer in these areas.

Cavity-assisted emission of polarization-entangled photons from biexcitons in quantum dots with fine-structure splitting - Schumacher, Stefan; Förstner, Jens; Zrenner, Artur; Florian, Matthias; Gies, Christopher; Gartner, Paul; Jahnke, Frank (Optics Express)
We study the quantum properties and statistics of photons emitted by a quantum-dot biexciton inside a cavity. In the biexciton-exciton cascade, fine-structure splitting between exciton levels degrades polarization-entanglement for the emitted pair of photons. However, here we show that the polarization-entanglement can be preserved in such a system through simultaneous emission of two degenerate photons into cavity modes tuned to half the biexciton energy. Based on detailed theoretical calculations for realistic quantum-dot and cavity parameters, we quantify the degree of achievable entanglement.
Keywords: tet_topic_qd

Dynamics of ionisation and entanglement in the 'atom + quantum electromagnetic field' system - Sharapova, Polina; Tikhonova, O V (Quantum Electronics)
Keywords: Electrical and Electronic Engineering; Atomic and Molecular Physics; and Optics; Statistical and Nonlinear Physics; Electronic; Optical and Magnetic Materials

Optimization of the intensity enhancement in plasmonic nanoantennas - Hildebrandt, Andre; Reichelt, Matthias; Meier, Torsten; Förstner, Jens
We design the geometrical shape of plasmonic nanostructures to achieve field patterns with desired properties. For this, we combine Maxwell simulations and automatic optimization techniques. By allowing variations of the geometrical shape, which can be based on either boxes or arbitrary polygons, we maximize the desired objective.
Keywords: tet_topic_optical antenna; tet_topic_plasmonics